Transcriptome-wide characterization of bHLH transcription factor genes in Lycoris radiata and functional analysis of their response to MeJA - Wang, Ning; Shu, Xiaochun; Zhang, Fengjiao; Wang, Zhong (Frontiers in Plant Science, 2023)
Plant basic helix–loop–helix (bHLH) transcription factor (TF), one of the biggest specific TF families, plays significant roles in plant growth, development, and abiotic stress responses. However, there has been minimal research about the effects of MeJA treatment on the bHLH gene family in Lycoris radiata (L’Her.) Herb. In this study, 50 putative LrbHLH genes with complete open reading frames (ORFs), which were divided into 20 bHLH subfamilies, were identified from the L. radiata transcriptome sequence data. The Multiple EM for Motif Elicitation (MEME) analysis showed that the conserved motif 1 and motif 2 constituted the most conserved bHLH domain and distributed in the most of LrbHLHs. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis of LrbHLH genes revealed their involvement in regulation of plant growth, jasmonic acid (JA) mediated signaling pathway, photoperiodism, and flowering. Subcellular localization analysis exhibited that most LrbHLHs were localized in the nucleus. Expression pattern analysis of different tissues and flower developmental stages of L. radiata suggested that LrbHLH genes expression differed across lineages and might be important for plant growth and organ development in Lycoris. All LrbHLH genes exhibited specific spatial and temporal expression patterns under MeJA treatment at different times. Moreover, LrbHLHs interacted with jasmonate ZIM (zinc-finger inflorescence meristem) domain (JAZ) proteins by the protein-protein interaction (PPI) networks and the yeast two-hybrid system analysis, indicating the expression of LrbHLHs are positively correlated with JA signaling pathway. Our results provide insights for further investigation of LrbHLHs to find their functions and regulatory mechanisms involved in JA signaling pathway.